Effects of different sperm sources on the clinical outcomes of in vitro oocyte maturation cycles combined with intracytoplasmic sperm injection - Li, Jianhua; Chen, Jing; Tian, Shuang; Jiao, Tingting; Wang, Jianye; Wei, Yan; Cheng, Yanbin; Xu, Ye; Chian, Ri-Cheng; Li, Youzhu; Zhang, Shuiwen (Frontiers in Endocrinology, 2023)
Objectives: To evaluate the embryonic developments and clinical outcomes of different sperm sources with cycles of intracytoplasmic sperm injection (ICSI) and in vitro maturation (IVM). Methods: This retrospective study was approved by the hospital ethics committee and conducted in the hospital in vitro fertilization (IVF) clinic. From January 2005 to December 2018, 239 infertile couples underwent IVM-ICSI cycles and were divided into three groups according to different sperm sources. Group 1 comprised patients with percutaneous caput epididymal sperm aspiration (PESA, n=62, 62 cycles), group 2 comprised patients with testicular sperm aspiration (TESA, n=51, 51 cycles), and group 3 comprised patients with ejaculated sperm (n=126, 126 cycles). We calculated the following outcomes: (1) outcomes per IVM-ICSI cycle: fertilization rate, cleavage rate, and embryo quality; (2) outcomes per embryo transfer cycle: endometrial thickness, implantation rate, biochemical pregnancy rate, clinical pregnancy rate, and live birth rate. Results: There was no difference in basic characteristics among the three groups, such as the female partner’s age, basal FSH, basal LH, and antral follicle count (P>0.1). There were no statistically significant differences according to IVM-ICSI cycle among the three groups in fertilization rate, cleavage rate, and rate of good-quality embryos (P>0.05). The results were similar among cycles regarding the number of transfer embryos and endometrial thickness per embryo transfer cycle among the three groups (P>0.05). There were also similar clinical outcomes per embryo transfer cycle among the three groups, such as the biochemical pregnancy rate, clinical pregnancy rate, and live birth rate (P>0.05). Conclusions: Different sperm sources (percutaneous caput epididymal sperm aspiration, testicular sperm aspiration, ejaculated sperm) do not affect the embryo and clinical outcomes after IVM-ICSI cycles. Keywords: percutaneous epididymal sperm aspiration (PESA); testicular sperm aspiration (TESA); ejaculated sperm; vitro maturation (IVM); intracytoplasmic sperm injection (ICSI);